Aiming for the biodiversity target with the social welfare arrow: medicinal and other useful plants from a Critically Endangered grassland ecosystem in Limpopo Province, South Africa. Issue 1 (2nd January 2017) - Dzerefos, Cathy M.; Witkowski, Ed T.F.; Kremer-Köhne, Sylvie
ABSTRACT: Underprivileged communities rely on beneficial plants for medicinal and cultural purposes as well as income generation. They are marginalised by land use planners, politicians and municipalities, resulting in biased integrated development and increased poverty. A case in point, is the Critically Endangered Woodbush Granite Grassland (WGG) in Limpopo Province, South Africa. The WGG has high plant biodiversity (661 species in 192 ha), which includes 18 Red Listed taxa and 36 taxa protected by existing legislation. Although 18% of the plant species have medicinal properties and the area is a source of plants used for medicine and hand brushes, this is the first ethnobotanical study to be undertaken here. Structured interview schedules were conducted with 54 people who were using plants from the area, and a list of the top 20 medicinal plants was compiled. Respondents raised concerns regarding the impact of fire management and 69% of traditional healers noted increasing difficulty in finding useful plants in the last decade. The majority of plant harvesters supported choices related to protecting the ecosystem. Propagated plants were considered to be an option by 60% of plant harvesters but serious risks to success were raised, suggesting that in situ biodiversity preservation was key to securing traditional healthcare and cultural practice. The socio-ecological system that exists is described and requires recognition by state bodies responsible for conservation and social welfare.